2016
DOI: 10.1523/jneurosci.0157-16.2016
|View full text |Cite|
|
Sign up to set email alerts
|

Cholinergic Interneurons Use Orbitofrontal Input to Track Beliefs about Current State

Abstract: When conditions change, organisms need to learn about the changed conditions without interfering with what they already know. To do so, they can assign the new learning to a new "state" and the old learning to a previous state. This state assignment is fundamental to behavioral flexibility. Cholinergic interneurons (CINs) in the dorsomedial striatum (DMS) are necessary for associative information to be compartmentalized in this way, but the mechanism by which they do so is unknown. Here we addressed this quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 57 publications
3
85
2
Order By: Relevance
“…And more recent work has suggested the OFC might also utilize or perhaps even encode these relationships (Bradfield et al, 2015; Saez et al, 2015; Schuck et al, 2016; Stalnaker et al, 2016; Wilson et al, 2014). For example, associative event-driven firing in the OFC is often specific to the cue-reward combinations appropriate for a given context or set of trials (Saez et al, 2015; Schoenbaum et al, 1999; Thorpe et al, 1983), and in one particularly nice set of parallel studies, ensembles of neurons in the OFC (Farovik et al, 2015) and the hippocampus (Komorowski et al, 2013; McKenzie et al, 2014; McKenzie et al, 2016) were found to encode a hierarchy of feature representations in rats performing a decision making task, with neurons in each area encoding abstract aspects of the task, such as the context-dependent linkages between odor cues and reward.…”
Section: Discussionmentioning
confidence: 99%
“…And more recent work has suggested the OFC might also utilize or perhaps even encode these relationships (Bradfield et al, 2015; Saez et al, 2015; Schuck et al, 2016; Stalnaker et al, 2016; Wilson et al, 2014). For example, associative event-driven firing in the OFC is often specific to the cue-reward combinations appropriate for a given context or set of trials (Saez et al, 2015; Schoenbaum et al, 1999; Thorpe et al, 1983), and in one particularly nice set of parallel studies, ensembles of neurons in the OFC (Farovik et al, 2015) and the hippocampus (Komorowski et al, 2013; McKenzie et al, 2014; McKenzie et al, 2016) were found to encode a hierarchy of feature representations in rats performing a decision making task, with neurons in each area encoding abstract aspects of the task, such as the context-dependent linkages between odor cues and reward.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the influence of such state representations may be ubiquitous once one begins to look for it. Event-related firing the OFC as well as other prefrontal areas and even amygdala is influenced by context or state defined as trial blocks with different reward contingencies (Saez et al, 2015; T A Stalnaker et al, 2014), and cholinergic interneurons in the dorsal striatum provide an OFC-dependent state correlate that distinguishes such different blocks of trials (Stalnaker et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Recording of CINs in rats performing a behavioral task consisting of several trial blocks referred as ‘state’ which requires the recall of the current state and the learning of changed conditions have shown that dorsomedial but not dorsolateral striatal CINs are essential for the animal to keep track of the current behavioral trial or state. This state information is dependent on orbitofrontal cortex input to CINs (Stalnaker et al ., ). Those results are consistent with observations showing involvement of CINs in flexible behaviors and in integrating new learning (Ragozzino et al ., ; Bradfield et al ., ; Aoki et al ., ).…”
Section: Glutamatergic Input To Striatal Interneuronsmentioning
confidence: 99%